AUDITORS' LIABILITY AND ITS IMPACT ON THE EUROPEAN FINANCIAL MARKETS - Doralt, Walter; Hellgardt, Alexander; Hopt, Klaus J.; Leyens, Patrick C.; Roth, Markus; Zimmermann, Reinhard (Cambridge law journal, 2008)
In 2007 the European Commission produced a Staff Working Paper seeking consultation on the development of auditors' liability in Europe. The present article represents the views of the Working Group on the subject set up by the Max Planck Institute for Comparative and International Private Law in Hamburg.